2021
DOI: 10.1177/1098612x211037431
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effect of phenobarbital administration on the biochemistry profile, with a focus on serum liver values, in epileptic cats

Abstract: Objectives Phenobarbital (PB) is the most common antiseizure drug (ASD) used for the management of feline epilepsy. In dogs, PB is known to cause serum liver enzyme induction and hepatotoxicity, especially after administration long term or in high concentrations. In cats, insufficient evidence is available to draw similar conclusions. The aim of this study was to evaluate the effect of PB administration on the serum biochemistry profile of epileptic cats. As an additional objective, other adverse effects arisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Elevation of liver enzyme activity (not otherwise specified) was observed in two cats, of which one received PB and ZNS and the other received PB and DZP. PB sometimes causes elevated alanine transferase levels in cats ( Finnerty et al , 2014 ; Hermans et al , 2022 ), therefore elevation of liver enzyme observed in this study possibly is explained by the use of PB. ZNS has also been reported to induce elevation of the levels of liver enzymes, especially alkaline phosphatase, in dogs ( Klopmann et al , 2007 ; Boothe and Perkins, 2008 ; Dewey et al , 2014 ; Smith et al , 2022 ) but the exact mechanism of why this elevation of liver enzyme occurs is still undetermined.…”
Section: Discussionmentioning
confidence: 55%
“…Elevation of liver enzyme activity (not otherwise specified) was observed in two cats, of which one received PB and ZNS and the other received PB and DZP. PB sometimes causes elevated alanine transferase levels in cats ( Finnerty et al , 2014 ; Hermans et al , 2022 ), therefore elevation of liver enzyme observed in this study possibly is explained by the use of PB. ZNS has also been reported to induce elevation of the levels of liver enzymes, especially alkaline phosphatase, in dogs ( Klopmann et al , 2007 ; Boothe and Perkins, 2008 ; Dewey et al , 2014 ; Smith et al , 2022 ) but the exact mechanism of why this elevation of liver enzyme occurs is still undetermined.…”
Section: Discussionmentioning
confidence: 55%
“…7,8 Furthermore, the effect of PB on the liver is well known, leading to hepatic enzyme induction; however, these changes have not been observed in cats. 9 Compared with a study in PB-treated dogs by Pakozdy et al…”
Section: Discussionmentioning
confidence: 99%
“…The most common are cytopenia, lymphadenopathy, pseudolymphoma, skin eruptions, pyrexia, and coagulopathy 7,8 . Furthermore, the effect of PB on the liver is well known, leading to hepatic enzyme induction; however, these changes have not been observed in cats 9 …”
Section: Discussionmentioning
confidence: 99%
“…Phenobarbital (PB) is the drug of choice for long-term treatment of epilepsy but it exerts some undesirable side effects 5,7 . This study aimed to investigate whether CB or/and Vit-C have ameliorative effects against the hepatorenal toxicity that induced by PB-treatment.…”
Section: Discussionmentioning
confidence: 99%